The impact of COVID-19 vaccination on the risk of hospitalization in Fayoum healthcare workers - Abdallah Gebili, Shaimaa; Ali Abu El Hassab, Amal; Ibrahim Mohammed, Ashraf; Rohym, Asmaa; Gamal El-Din, Hatem; Abdelhamed Fathy, Mohamed; Mohamed Ahmed Abdelhafez, Ahmed; Younis Elsary, Asmaa (International Journal Of Community Medicine And Public Health, 2024)
Background: Healthcare workers (HCWs) face several challenges including treating COVID-19 patients. The immunization of the population through vaccination is recognized as a public health priority. The aim of the study is to assess the impact of vaccination on the risk of hospitalization and mortality in HCWs due to COVID-19 infection. Methods: This study was conducted in Egypt in El Fayoum governorate on the HCWs from April 2021 to the end of the year 2021. A cohort retrospective approach was carried out using (the national electronic disease surveillance system) NEDSS and COVID-19 vaccine registration system. Hospitalization is determined by assessment of the cases according to the protocol of COVID-19 management of MOHP November 2020. Results: There was no association between hospitalization and both sex and residence (p=0.1, and 0.06 respectively). There was no statistical significant association between hospitalization and vaccination (time, status, or type). The p=0.2, 0.6, and 0.07 respectively. Age and the presence of comorbidities were statistically significant predictors with p=0.004 and 0.04, respectively, as increasing age and the presence of comorbidities will increase the likelihood of hospitalization by 1.04 and 1.9 folds, respectively. Conclusions: This study shows no significant association between vaccination and hospitalization of HCWs.